GARDEN ARCHITECTONIC CHARACTERISTICS OF THE CITY IDENTITY - PolÃ¡ÄkovÃ¡, Lucie (European Scientific Journal, ESJ, 2014)
The research is focused on the relation between the city identity as a whole and its physical components with regard to the cultural-historical context of the relevant place. The individual components and their interactions have been defined and analyzed due to the place and on the basis of a thorough survey of the physiognomy of the urban open spaces. Set into a wider context of the Central European culture, the comparative results from the surveys of the examined cities could be understood as a conclusive and inspirational source for the future development of the urban open space.